Republic of Latvia : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Latvia's strong recovery has recently slowed in the face of sluggish growth in the euro area and deteriorating economic conditions in Russia amid rising geopolitical tensions. GDP growth decelerated to 2.4 percent in 2014 reflecting weak demand and the prolonged closure of a steel manufacturer. In 2015, the weak external environment, particularly the sharp slowdown in Russia, will continue to weigh on exports and investment. This is expected to be mitigated, but not fully offset, by higher disposable income owing to lower oil prices and robust real wages, the reopening of the steel manufacturer, and the accommodative monetary stance of the European Central Bank.